IFN-Gamma and TNF-Alpha as a Priming Strategy to Enhance the Immunomodulatory Capacity of Secretomes from Menstrual Blood-Derived Stromal Cells - María Ángeles de Pedro (MDPI AG, 2021)
Mesenchymal stromal cells isolated from menstrual blood (MenSCs) exhibit a potent pro-angiogenic and immunomodulatory capacity. Their therapeutic effect is mediated by paracrine mediators released by their secretomes. In this work, we aimed to evaluate the effect of a specific priming condition on the phenotype and secretome content of MenSCs. Our results revealed that the optimal condition for priming MenSCs was the combination of interferon gamma (IFNγ) and tumor necrosis factor alpha (TNFα) that produced a synergistic and additive effect on IDO1 release and immune-related molecule expression. The analyses of MenSC-derived secretomes after IFNγ and TNFα priming also revealed an increase in EV release and in the differentially expressed miRNAs involved in the immune response and inflammation. Proliferation assays on lymphocyte subsets demonstrated a decrease in CD4+ T cells and CD8+ T cells co-cultured with secretomes, especially in the lymphocytes co-cultured with secretomes from primed cells. Additionally, the expression of immune checkpoints (PD-1 and CTLA-4) was increased in the CD4+ T cells co-cultured with MenSC-derived secretomes. These findings demonstrate that the combination of IFNγ and TNFα represents an excellent priming strategy to enhance the immunomodulatory capacity of MenSCs. Moreover, the secretome derived from primed MenSCs may be postulated as a therapeutic option for the regulation of adverse inflammatory reactions.